Labor market developments in China: A neoclassical view - Suqin Ge; Dennis Tao Yang (Institute for the Study of Labor (IZA), 2010)
This paper assesses the applicability of two alternative theories in understanding labor market developments in China: the classical view featuring a Lewis turning point in wage growth versus a neoclassical framework emphasizing rational choices of individuals and equilibrating forces of the market. Empirical evidence based on multiple data sources fails to validate the arrival of the Lewis turning point in China, showing continuous and coordinated wage growth across rural and urban sectors instead. Consistent with the neoclassical view, we find that rural workers expanded off-farm work when mobility restrictions were lifted, interprovincial migration responded to expected earnings and local employment conditions, and returns to education converged gradually to the international standard. These findings suggest major progresses in the integration of labor markets in China.
Keywords: J31; J21; O11; 330; labor markets; rural-urban migration; wage growth; schooling returns; Lewis turning point; China